Factors Associated with Post-Stroke Fatigue Among Patients with Acute Ischemic Stroke - Rakkaew, Supachai; Kummarg, Urai (Nursing Journal CMU, 2024)
Post-stroke fatigue (PSF) is a key factor in post-stroke recovery. This descriptive correlation research aimed to study the factors associated with PSF in acute ischemic stroke patients. The participants were purposely selected to include 97 patients diagnosed with acute ischemic stroke who were over 18 years old and had stable symptoms while receiving services at Thammasat University Hospital. The instruments used in the research included a demographic characteristics’ questionnaire, the Fatigue Severity Score (FSS), the Numerical Pain Rating Scale (NRS), the Athens Insomnia Scale: (AIS-Thai), the Barthel Activities of Daily Living (ADL), the Hospital Anxiety and Depression Scale (HADs), and the Stress Test Questionnaire (ST-5). All instruments were tested for reliability, which was .96, 1.00, .86, .88, .81, .86, and .86, respectively. Data analysis used descriptive statistics and Pearson correlation statistics. The results found that the participants consisted of equal numbers of males and females, with an average age of 64.44 years (SD = 11.28). Post-stroke period ranged from 1-13 days (Mean = 3.40, SD = 1.77), and 44.3% had fatigue after stroke (Mean = 3.76, SD = 1.42). The relationships between the FSS and the NRS, AIS-Thai, ADL, Anxiety, Depression, and ST-5 were statistically significant (r = .334, p < .01; r = .481, p < .01; r = -2.67, p < .01; r = .476, p < .01; r = .384, p < .01; and r = .469, p < .01, respectively). The results of this study can be used as basic information for planning care to prevent and manage PSF in patients with acute stroke.